Analisis Tindak Tutur Ekspresif Dalam Naskah DramaLaron Karya Gepeng Nugroho Dan Digunakan SebagaiInovasi Pembelajaran Bahasa Indonesia - Setyaningrum, Novita Almuthiah; , Dra. Atiqa Sabardila, M.Hum (2017)
This descriptive qualitative research aims to (1) identify the form of expressive speech acts in drama script entitled Laron by Gepeng Nugroho, (2) Describe expressive speech acts in drama script entitled Laron by Gepeng Nugroho, and (3) Associate expressive speech in drama script Laron by Gepeng Nugroho as an innovative Indonesian language learning. To achieve that goal, this research uses descriptive qualitative research design of pragmatic study. Technique of data collecting using technique of refer to and record technique. Data Data analysis using a pragmatic pran method with the technique of deciding elements or techniques PUP. The result of this research is expressive speech in Laron drama script by Gepeng Nugroho found 48 speeches. The form of expressive speech acts in the drama Laron works by Gepeng Nugroho is divided into 8 categories, namely: (1) direct speech acts found 40 speeches, (2) indirect speech acts found 8 speech, (3) literal speech act found 39 speeches, (4) nonliteral speech act is found 9 speech, (5) direct literal speech acts found 33 speech, (6) direct non literal speech acts found 6 speech, (7) indirect non literal speech acts found 7 speech, and (8) Indirect non literal speech acts found 2 speech. There are 7 intentions of expressive speech act in laron drama script include: complaining found 17 speeches, criticism found 6 speeches, praising found 14 speeches, blame found 4 speeches, apologized found 3 speeches, congratulated found 2 speech, and thanked found 2 Speech. The relevance of expressive speeches of drama laron works of gepeng nugroho as an innovative learning material in Indonesia is related to the learning of SMP class VIII with KD 8.1 writing creative drama script one round by paying attention to the authenticity of the idea. Laron drama script can be used as teacher teaching materials on the KD by using different innovations in order to achieve the learning objectives.